Representaciones de la naturaleza en la Amazonía ecuatoriana: ¿subsistencia local o conservación global? - Neira Brito, Francisco (2006)
Native and western cultural representations of nature are analyzed in a multidisciplinary perspective in the geographic context of the Ecuadorian Amazonia. This social and environmental dynamic has not been clearly understood, and the environmental management is neither efficient nor considered legitimate. For indigenous people nature transcends its intrinsic value and its uses are the basis of their economic subsistence. For Western civilization, a mercantilist vision of nature prevails. This vision is confronted, at the same time, by a biocentric approach that confers certain intrinsic values. The goal of this article is to expand the dialogue between these two visions in the process of designing and executing a coherent environmental policy within the existing complexity. Moreover, some concepts will be brought to answer one key question: Is it possible for Amazonian inhabitants to maintain their levels of natural resource use in a long term period considering globalization with-in a context of environmental concern?